Improving life quality for the aged: a comprehensive post-occupancy evaluation of long-term care facilities in China - Chen, Yu; Zhang, Jiamin; Yang, Zhuohang; Qiu, Zhi (Frontiers in Public Health, 2024)
IntroductionIn response to the call for active aging, improving the quality of residential environments for older people is becoming a worldwide concern. Over the past decade, China has witnessed a significant increase in the construction of long-term care facilities (LTCFs) catering to the older adult with physical and mental limitations. However, the fast pace of LTCF development has led to substandard physical environments that compromise the quality of life for older individuals. Consequently, there is an urgent need to conduct comprehensive post-occupancy evaluations (POEs) in order to systematically assess the current state of LTCF physical environments and identify prevailing problems therein.MethodsThis study conducted POEs on 37 existing LTCFs from both objective and subjective perspectives, using self-developed environmental assessment tools and user satisfaction questionnaires.ResultsThe results reveal substantial room for improvement within LTCF physical environments, particularly concerning outdoor areas, resident rooms and staff spaces. The psychological needs of residents and working requirements of staff are not adequately addressed or supported.DiscussionA total of ninety-two typical problems are identified across eight categories, and relevant causes associated with programming, design, construction, and operation are discussed. The findings are expected to serve as warnings for future designs, provide empirical evidence for the revision of relevant standards, and promote the sustainable development of LTCF construction.